If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(x+3)+3=6(x+3)+7
We move all terms to the left:
-4(x+3)+3-(6(x+3)+7)=0
We multiply parentheses
-4x-(6(x+3)+7)-12+3=0
We calculate terms in parentheses: -(6(x+3)+7), so:We add all the numbers together, and all the variables
6(x+3)+7
We multiply parentheses
6x+18+7
We add all the numbers together, and all the variables
6x+25
Back to the equation:
-(6x+25)
-4x-(6x+25)-9=0
We get rid of parentheses
-4x-6x-25-9=0
We add all the numbers together, and all the variables
-10x-34=0
We move all terms containing x to the left, all other terms to the right
-10x=34
x=34/-10
x=-3+2/5
| 1/2(6x+8)=2x+4x | | 9n-5+n=-5+10n | | 5x+10=24–2x | | 0.7x+0.6=0.5x-0.29 | | 4*p+2=3*p-7 | | 3c+6+c=4+c | | 49x^2+6=87 | | X=24-24,y=24 | | 69=(23)^x | | 8-5x=-2x+1 | | -150=5x-4(-2x+18) | | 3c+6-c=4+c | | 6.4x-5.1x=-3.25 | | 4x-7=x+3(X+4) | | 2x-20+7=x-2 | | 7x+3=67-x | | 2(x-3/5)+1/4=-3/4(x+1) | | 1=–(–w+6) | | 82=4+6(r+5) | | 3m-10=2(4m-2) | | 35-(w+8)=13 | | 0.4x+21=-0.2(8x-25)-2x | | 69=23^x | | 2p+1.5*1.5=11.50 | | 12n+10=60 | | 144=x/12 | | 7(3x-7)+3=80 | | 7+3(2x-5)=15 | | X=4y-90 | | x–9=–15 | | w+8=13 | | 90=4x+1/2x^2 |